2015
DOI: 10.13189/aep.2015.030101
|View full text |Cite
|
Sign up to set email alerts
|

Pongamia Pinnata as Alternate Liquid Dielectrics in Distribution Transformer: A Critical Study on the Property of Viscosity

Abstract: Distribution Transformers are one of the imperative equipment in power system. The insulation design has an important role because it continuously energizes in a day. Due to electro mechanical stresses the operating temperature of distribution transformer will be increased which maintains with in limit using liquid dielectrics. Traditional mineral oil is used as liquid dielectrics in Distribution Transformer. Due to lack of fossil fuels and lesser biodegradability characteristics of mineral oil, the alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Masarakall et al concluded that the characteristics of Pongamia pinnata liquid may be enhanced by the esterification method and by using additives for pour point and oxidation stability; consequently, it may be regarded as the dielectric liquid for transformers [ 147 ]. Alternatively, Mariprasath et al mentioned that Pongamia pinnate-based liquids indicate superior BDV than MO and adequate viscosity to be applied liquid insulation for transformers [ 148 ].…”
Section: New and Innovative Technologies For Environmentally Frienmentioning
confidence: 99%
“…Masarakall et al concluded that the characteristics of Pongamia pinnata liquid may be enhanced by the esterification method and by using additives for pour point and oxidation stability; consequently, it may be regarded as the dielectric liquid for transformers [ 147 ]. Alternatively, Mariprasath et al mentioned that Pongamia pinnate-based liquids indicate superior BDV than MO and adequate viscosity to be applied liquid insulation for transformers [ 148 ].…”
Section: New and Innovative Technologies For Environmentally Frienmentioning
confidence: 99%
“…During transesterification, reaction kinematics will result into variation in dielectric property of the reactants. Summarizing the analysis reported in literature [31][32][33][34][35], the apparent relative permittivity of the sample at an angular frequency ω can be considered as consisting of () (1) rpol   has a value appreciably different from zero, only in the range of frequencies around the inverse of the characteristic time of the relaxation process. Third term is related to the dissipation due to charge transport…”
Section: A Electrical Impedance Analysis Of Capacitive Sensorsmentioning
confidence: 96%
“…The relative permittivity or dielectric property of reaction mixture is the key factor when the transesterification progress is to be monitored by capacitive sensors. Karanja oil exhibits a good dielectric property and Analysis and experimentations carried by T. Mariprasath et al [35] reveal that the viscosity of Karanja oil is low compared to soybean, coconut and sunflower oil and tits average dielectric breakdown strength is very high. The moisture content also reduces when stored.…”
Section: A Electrical Impedance Analysis Of Capacitive Sensorsmentioning
confidence: 99%
“…Summarize the existing problems in the research on the remaining life prediction of the oil-paper insulation of transformers: (1) The oil-paper insulation deterioration model based on the deterioration test and mathematical theory lacks consideration of the randomness of the deterioration process and the uncertainty of the remaining life prediction, and the application conditions are limited; (2) The Weibull distribution model and the prediction method of the remaining life of the transformer oil-paper insulation based on machine learning have high requirements on the number of samples; (3) The equipment deterioration model based on the traditional Wiener stochastic process cannot well adapt to the large changes in the early data of the deterioration. In the case of non-linear degradation process, the uncertainty of the remaining life prediction results is high.…”
Section: Introductionmentioning
confidence: 99%
“…AS the core equipment of the power system, the operating life of the oil-immersed transformer is of great significance to the reliable power supply of the power grid [1][2][3]. The purpose of performance degradation analysis and remaining life estimation of the transformer is to predict its degradation trend and end of life, so that maintenance measures can be taken before the end of the transformer life to avoid power outage accidents.…”
Section: Introductionmentioning
confidence: 99%